Wear-resistant 3C epoxy glass fiber composite board and manufacturing process thereof

By using phenolic resin as a curing agent and adding vapor-phase silica in the epoxy glass fiber composite board, the problem of insufficient wear resistance in the prior art is solved, and the wear resistance and service life are significantly improved , reduces production costs.

CN119502481APending Publication Date: 2025-02-25ZHEJIANG YUANJI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411646422.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The wear resistance of existing epoxy fiber composite boards is low, resulting in a high frequency of gasket replacement during the wear and brushing of mobile phone lenses, which increases production costs and material consumption.

Method used

Phenolic resin is used as the curing agent and vapor-phase silica is added to the glue to form a tighter cross-linked mesh structure and higher viscosity, which significantly enhances the wear resistance of the composite panel.

Benefits of technology

It significantly improves the wear resistance of epoxy glass fiber composite board, extends the service life of the gasket, and reduces production costs and material consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a wear-resistant 3C epoxy glass fiber composite board and a manufacturing process thereof, and relates to the technical field of composite board manufacturing, the 3C epoxy glass fiber composite board comprises a steel plate, a release film, a prepreg, a release film and a steel plate from top to bottom; the prepreg raw materials comprise glass fiber cloth and glue; the glue is prepared from the following raw materials: 49 to 63 parts of epoxy resin, 15 to 25 parts of phenolic resin, 0.003 to 0.01 part of imidazole accelerant, 20 to 30 parts of solvent and 3 to 6 parts of fumed silica. Coating glue on the glass fiber cloth, and baking for 4-6 minutes at the temperature of 170-190 DEG C to obtain a prepreg; a steel plate, a release film, a prepreg, a release film and a steel plate which are the same in size are sequentially overlaid and then subjected to hot pressing and bonding through a hot press, and then the wear-resistant 3C epoxy glass fiber composite plate is obtained. The 3C epoxy glass fiber composite board provided by the invention has relatively high strength and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of composite board manufacturing technology, and in particular to a wear-resistant 3C epoxy glass fiber composite board and its manufacturing process. Background Art

[0002] A crucial step in the manufacturing process of mobile phone glass lenses is the fine brushing of their surfaces. This step is designed to ensure that the lenses have extremely high optical clarity and flatness to meet the high standards required of cameras and displays in modern smartphones. During this precision processing, in order to effectively protect the lenses from direct wear and control the brushing force, a layer of gasket is usually placed between the lens and the brushing tool. The ideal gasket material not only needs to have good flexibility and stability, but also must be softer than glass to avoid any scratches or damage to the lenses during the brushing process.

[0003] At present, a widely used gasket material in the industry is epoxy glass fiber composite board, which combines the adhesiveness of epoxy resin and the reinforcing effect of glass fiber, and can provide certain wear resistance and structural strength. The epoxy glass fiber composite board in the prior art generally uses traditional dicyandiamide as a curing agent, and its wear resistance has obvious limitations, and can only reach an average of about 7,500 times of wear. Therefore, in the large-scale production of mobile phone lenses, the replacement frequency of gaskets is relatively high, which not only increases the downtime and labor costs in the production process, but also leads to a significant increase in material consumption, thereby greatly pushing up the overall manufacturing cost. Therefore, continuing to provide wear-resistant epoxy glass fiber composite boards can significantly increase the number of wear times. Summary of the invention

[0004] In order to improve the wear resistance of the epoxy glass fiber composite board, the present application provides a wear-resistant 3C epoxy glass fiber composite board and a manufacturing process thereof.

[0005] The present application provides a wear-resistant 3C epoxy glass fiber composite board, which adopts the following technical solution: A wear-resistant 3C epoxy glass fiber composite board, the 3C epoxy glass fiber composite board comprises a steel plate, a release film, a prepreg, a release film, and a steel plate from top to bottom; the prepreg raw materials include glass fiber cloth and glue; The glue raw materials include 49-63 parts of epoxy resin, 15-25 parts of phenolic resin, 0.003-0.01 parts of imidazole accelerator, 20-30 parts of solvent, and 3-6 parts of fumed silica; The structure of the composite panel is as follows:

[0006] By adopting the above-mentioned technical scheme, the present application adopts phenolic resin as a curing agent, and the product molecules are presented in a cross-linked network structure, which makes the product tighter and more resistant to abrasion and brushing, thereby significantly enhancing the strength and wear resistance of the composite board; adding fumed silica to the glue not only increases the viscosity of the glue, improves the viscosity between the semi-cured sheet and the steel plate and the release film, but also can improve the tensile strength of the semi-cured sheet, effectively enhancing the wear resistance of the composite board.

[0007] Preferably, the epoxy resin is composed of the following raw materials in parts by weight: 45-55 parts of epoxy resin with an epoxy equivalent of 500-600 g / eq and 4-8 parts of macromolecular epoxy resin.

[0008] By adopting the above technical scheme, the glue for preparing the semi-cured sheet in the present application adopts a compound of epoxy resin with an epoxy equivalent of 500-600g / eq and a macromolecular epoxy resin to form a more balanced curing system, which can not only effectively enhance the viscosity of the semi-cured sheet, but also significantly increase the strength and toughness of the epoxy glass fiber composite board, and greatly enhance the wear resistance of the epoxy glass fiber composite board.

[0009] Preferably, the macromolecular epoxy resin is composed of the following raw materials in parts by weight: 80-90 parts of bisphenol A, 10-20 parts of epichlorohydrin, 0.2-0.5 parts of alkaline water, and 30-40 parts of acetone.

[0010] Preferably, the alkaline water is an aqueous solution of alkali with a mass fraction of 20-40%.

[0011] Preferably, the alkali is a mixture of one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate and potassium bicarbonate.

[0012] Preferably, the method for preparing the macromolecular epoxy resin comprises the following steps: Mix bisphenol A, epichlorohydrin and alkaline water, and react at 75-85°C for 4-6 hours. After the reaction, remove the base at 105-120°C for 4-6 hours. After cooling to 65-75°C, add acetone and continue stirring for 1-2 hours to obtain a macromolecular epoxy resin.

[0013] By adopting the above technical scheme, a macromolecular epoxy resin with a molecular weight of about 40,000 to 45,000 containing a large amount of benzene rings is prepared, which has strong adhesion and mechanical strength, thereby significantly enhancing the strength and wear resistance of the epoxy glass fiber composite board.

[0014] Preferably, the method for preparing the glue comprises the following steps: The epoxy resin, phenolic resin, imidazole accelerator, solvent and fumed silica are mixed and stirred for 5-9 hours to obtain glue.

[0015] Preferably, the method for preparing the prepreg comprises the following steps: The glass fiber cloth is coated with glue and baked at a temperature of 170-190°C for 4-6 minutes to obtain a semi-cured sheet.

[0016] The present application provides a manufacturing process for a wear-resistant 3C epoxy glass fiber composite board, which adopts the following technical solution: A manufacturing process of a wear-resistant 3C epoxy glass fiber composite board comprises the following steps: After stacking steel plates, release films, prepregs, release films, and steel plates of the same size in sequence and hot-pressing and bonding them with a hot press, a wear-resistant 3C epoxy glass fiber composite board is obtained.

[0017] Preferably, the temperature of the hot press is 150-170° C., the hot pressing time is 60-80 minutes, the pressure is 15-30 kg, and the cold pressing time is 60-80 minutes.

[0018] In summary, the present application includes at least one of the following beneficial technical effects: 1. This application uses phenolic resin as a curing agent, and the product molecules are presented in a cross-linked network structure, making the product more compact and more resistant to abrasion and brushing, thereby significantly enhancing the strength and wear resistance of the composite board; adding fumed silica to the glue not only increases the viscosity of the glue, improves the viscosity between the prepreg and the steel plate and the release film, but also improves the tensile strength of the prepreg, effectively enhancing the wear resistance of the composite board; 2. By adopting the above-mentioned technical scheme, the glue for preparing the semi-cured sheet in the present application adopts a compound of epoxy resin with an epoxy equivalent of 500-600g / eq and a macromolecular epoxy resin to form a more balanced curing system, which can not only effectively enhance the viscosity of the semi-cured sheet, but also significantly increase the strength and toughness of the epoxy glass fiber composite board, and greatly enhance the wear resistance of the epoxy glass fiber composite board. DETAILED DESCRIPTION

[0019] The present application is further described in detail below with reference to the embodiments. Example

[0020] Example 1 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0021] Example 2 S1. 85g of bisphenol A, 15g of epichlorohydrin, and 0.35g of a 20% sodium hydroxide solution were mixed and reacted at 80°C for 5h; after the reaction, the mixture was de-alkalized at 115°C for 5h; after the temperature was lowered to 70°C, 35g of acetone was added and the mixture was stirred for 1.5h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0022] Example 3 S1. After mixing 90g of bisphenol A, 20g of epichlorohydrin and 0.5g of 20% sodium hydroxide solution, the mixture was reacted at 85°C for 6h; after the reaction, the mixture was de-alkalized at 120°C for 6h; after cooling to 75°C, 40g of acetone was added and the mixture was stirred for 2h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0023] Example 4 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 50 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 6 g of a macromolecular epoxy resin prepared by S1, 20 g of a phenolic resin, 0.006 g of an imidazole accelerator, 25 g of an acetone solvent, and 4.5 g of fumed silica were mixed and stirred for 7 h to obtain a glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0024] Example 5 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2 55g of epoxy resin having an epoxy equivalent weight of 500g / eq, 8g of macromolecular epoxy resin prepared by S1, 25g of phenolic resin, 0.01g of imidazole accelerator, 30g of acetone solvent, 6g of fumed silica were mixed and stirred for 9h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0025] Example 6 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.9g / cm 2 , and baked at a temperature of 180°C for 5 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0026] Example 7 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 1.0g / cm 2 , and baked at a temperature of 190°C for 6 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0027] Example 8 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 160°C, the hot pressing time is 70 minutes, the pressure is 25kg, and the cold pressing time is 70 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0028] Example 9 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 170°C, the hot pressing time is 80 minutes, the pressure is 30kg, and the cold pressing time is 80 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0029] Example 10 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 30% sodium bicarbonate solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0030] Embodiment 11 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 40% potassium bicarbonate solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0031] Example 12 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 49 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 0 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 3 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0032] Comparative Example Comparative Example 1 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 0 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0033] Comparative Example 2 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 1 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0034] Comparative Example 3 S1. 80g of bisphenol A, 10g of epichlorohydrin, and 0.2g of a 20% sodium hydroxide solution were mixed and reacted at 75°C for 4h; after the reaction, the mixture was de-alkalized at 105°C for 4h; after the temperature was lowered to 65°C, 30g of acetone was added and the mixture was stirred for 1h to obtain a macromolecular epoxy resin; S2. 45 g of epoxy resin having an epoxy equivalent weight of 500 g / eq, 4 g of the macromolecular epoxy resin prepared by S1, 15 g of phenolic resin, 0.003 g of imidazole accelerator, 20 g of acetone solvent, and 8 g of fumed silica were mixed and stirred for 5 h to obtain glue; S3. Apply glue made from S2 on E-grade 7628 glass fiber cloth, average 0.8g / cm 2 , and baked at a temperature of 170°C for 4 minutes to obtain a prepreg; S4. After stacking the steel plate, release film, prepreg, release film and steel plate of the same size in sequence, they are hot-pressed and bonded by a hot press. The working temperature of the hot press is 150°C, the hot pressing time is 60 minutes, the pressure is 15kg, and the cold pressing time is 60 minutes, thus obtaining a wear-resistant 3C epoxy glass fiber composite board.

[0035] Performance testing 1. The tensile strength of the epoxy glass fiber composite panels obtained in Examples 1-12 and Comparative Examples 1-3 was tested using GB / T 528-2009 “Standard for Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber”. The results are shown in Table 1.

[0036] 2. The surfaces of the epoxy glass fiber composite panels obtained in Examples 1-12 and Comparative Examples 1-3 were subjected to a steel wool abrasion test under an external force of 1 kg. The results are shown in Table 1.

[0037] The specific test results are as follows: Table 1 Performance test results Tensile strength / MPa Wear times / 10,000 times Example 1 71.3 1.5 Example 2 74.5 1.7 Example 3 73.4 1.6 Example 4 77.6 2.0 Example 5 74.0 1.6 Example 6 73.8 1.7 Example 7 72.1 1.6 Example 8 72.8 1.6 Example 9 70.8 1.5 Example 10 72.3 1.5 Embodiment 11 71.7 1.5 Example 12 43.5 1.1 Comparative Example 1 35.6 0.80 Comparative Example 2 40.4 0.95 Comparative Example 3 41.1 1.0 It can be seen from the test results of Examples 1-11 that the 3C epoxy glass fiber composite board provided in the present application can withstand wear times of 15,000 to 20,000 times, indicating that the 3C epoxy glass fiber composite board provided in the present application has strong wear resistance; the tensile strength of the composite board can reach 70 MPa or more, indicating that the 3C epoxy glass fiber composite board provided in the present application has high mechanical properties.

[0038] It can be seen from the test results of Example 12 that when the epoxy resin with an epoxy equivalent of 500-600g / eq is added to the macromolecular epoxy resin for composite use, the strength and toughness of the composite board can be significantly increased, and the wear resistance of the composite board can be greatly enhanced; but when the macromolecular epoxy resin is not added, the tensile strength and wear resistance of the obtained composite board are significantly reduced.

[0039] It can be seen from the test results of Comparative Examples 1-3 that when fumed silica is added to the glue, the tensile strength and wear resistance of the composite board can be significantly increased, and the weight portion of the fumed silica is preferably 3-6 parts.

[0040] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A wear-resistant 3C epoxy glass fiber composite board, characterized by: The 3C epoxy glass fiber composite board includes a steel plate, a release film, a prepreg, a release film, and a steel plate from top to bottom; the prepreg raw materials include glass fiber cloth and glue; The glue raw materials include 49-63 parts of epoxy resin, 15-25 parts of phenolic resin, 0.003-0.01 parts of imidazole accelerator, 20-30 parts of solvent and 3-6 parts of fumed silica.

2. The wear-resistant 3C epoxy glass fiber composite board according to claim 1, characterized in that: The epoxy resin is composed of the following raw materials in parts by weight: 45-55 parts of epoxy resin with an epoxy equivalent of 500-600 g / eq and 4-8 parts of macromolecular epoxy resin.

3. The wear-resistant 3C epoxy glass fiber composite board according to claim 2, characterized in that: The macromolecular epoxy resin is composed of the following raw materials in parts by weight: 80-90 parts of bisphenol A, 10-20 parts of epichlorohydrin, 0.2-0.5 parts of alkaline water, and 30-40 parts of acetone.

4. The wear-resistant 3C epoxy glass fiber composite board according to claim 3, characterized in that: The alkaline water is an aqueous solution of alkali with a mass fraction of 20-40%.

5. The wear-resistant 3C epoxy glass fiber composite board according to claim 4, characterized in that: The alkali is a mixture of one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate and potassium bicarbonate.

6. The wear-resistant 3C epoxy glass fiber composite board according to claim 3, characterized in that: The preparation method of the macromolecular epoxy resin comprises the following steps: Mix bisphenol A, epichlorohydrin and alkaline water, and react at 75-85°C for 4-6 hours. After the reaction, remove the base at 105-120°C for 4-6 hours. After cooling to 65-75°C, add acetone and continue stirring for 1-2 hours to obtain a macromolecular epoxy resin.

7. The wear-resistant 3C epoxy glass fiber composite board according to claim 1, characterized in that: The preparation method of the glue comprises the following steps: The epoxy resin, phenolic resin, imidazole accelerator, solvent and fumed silica are mixed and stirred for 5-9 hours to obtain glue.

8. The wear-resistant 3C epoxy glass fiber composite board according to claim 1, characterized in that: The method for preparing the prepreg comprises the following steps: The glass fiber cloth is coated with glue and baked at a temperature of 170-190°C for 4-6 minutes to obtain a semi-cured sheet.

9. A process for producing a wear-resistant 3C epoxy glass fiber composite board according to any one of claims 1 to 8, characterized in that: The following steps are involved: After stacking steel plates, release films, prepregs, release films, and steel plates of the same size in sequence and hot-pressing and bonding them with a hot press, a wear-resistant 3C epoxy glass fiber composite board is obtained.

10. The wear-resistant 3C epoxy glass fiber composite board and its manufacturing process according to claim 9, characterized in that: The temperature of the hot press is 150-170° C., the hot pressing time is 60-80 minutes, the pressure is 15-30 kg, and the cold pressing time is 60-80 minutes.

Citation Information

Patent Citations

  • Wear-resisting high-molecular composite material

    CN102179981A

  • High-wear-resistance epoxy glass fabric laminated board and preparation method thereof

    CN113715422A